The Holmes Foundry Strike of March 1937: We'll Give Their Jobs to White Men! - Snow, Duart (Ontario History, 1977)
Examines the 1937 sit-down strike at the Holmes Foundry in Sarnia, Ontario, during which the strikers were beaten and . Discusses the impetus for the strike as well as the situation in the area and the foundry in particular. Comments on the strategy of the strikers and the stoking of racial hatred by the management and local authorities. The author argues that the Holmes Foundry strike illustrated the exent to which the elite was willing to go to crush the strike.
Keywords: Race; Strikes; Work